Intermittent delta waves mimicking inferior myocardial infarction - Yontar, Osman Can; Tenekecioglu, Erhan; Karaagac, Kermal; Tutuncu, Ahmet (Asian Journal of Medical Sciences, 2014)
Wolff-Parkinson-White syndrome is recognized with existence of delta waves and a short PR interval on electrocardiogram. Delta waves may appear positive or negative deviated on different derivations corresponding to the location of accessory pathway. In some cases, delta waves mimic Q waves which should be distinguished by physicians. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10802 Asian Journal of Medical Sciences Vol.6(1) 2015 115-116